PENGARUH TATA KELOLA PERUSAHAAN YANG BAIK DAN PROFITABILITAS TERHADAP TINGKAT PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA BANK SYARIAH DI INDONESIA - Deden Prasetyo; Ratna Purnama Sari (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2023)
The aim of this study is to analyse the impression of Good Corporate Governance component amount to Frequency of Sharia Supervisory Board Meeting, the Composition of Independent Commissioners Board, the Measure of the Board Directors, the Audit Committee Size and Profitability with the level of Corporate Social Responsibility (CSR) disclosure at Indonesia Sharia Banks in period 2017-2020. This research adopts quantitative method. The data population are 13 sharia general banks which are national private bank and there are 2 sharia general banks that are local government banks registered in OJK (the Financial Services Authority). The purposive sampling method is used as a sampling technique and get hold of 10 Sharia Banks. The samples in this study are 40 samples. Multiple Linear Analysis is utilized to test hypotheses in this research. Obtained results from this research that there was an influence between the Independent Commissioner’s Composition and Measure of the board Directors against the CSR level of disclosure at Indonesia Sharia Banks in period 2017-2020. Meanwhile, the Frequency of Sharia Supervisory Board Meetings, Audit Committee Size, and Profitability had no effect the CSR level of disclosure at Indonesia Sharia Banks in the period 2017-2020.